Testing for bubbles in agriculture commodity markets - Francisco José Areal; Kevin Balcombe; George Rapsomanikis (Economía Agraria y Recursos Naturales)
We apply the recent generalized sup augmented Dickey-Fuller (GSADF) test for explosive bubbles (Phillips et al., 2012) to monthly time-series for food, beverages, agricultural raw material, cereals, dairy, meat, oils and sugar indices and a total of 28 agricultural commodities between 1980-2012. We found price bubbles occurred for 6 out of the 10 indices studied and for 6 out of the 28 commodities within food markets. Results from the tests can help implementing policies aimed at mitigating effects of future price bubbles to targeted food commodity markets that may require special attention.